The Impact of Enterprise Systems on User Performance using the IGRACIAS V.1 Application at Telkom University Jakarta - Muftikhali, Qilbaaini Effendi; Kurniawan, Yudi Candra; Rahma, Dea Wemona (LPPM Telkom University Surabaya, 2024)
Telkom University Jakarta is a new educational institution, previously known as Institut Teknologi Telkom Jakarta. Telkom University Jakarta Campus obtained a legacy system called IGRACIAS V.1 as an education management software. The IGRACIAS V.1 application raised the question of whether legacy applications in new institutions can accelerate the flow of education management in pursuing competitors. This research provided a deeper exploration of the influence of legacy enterprise system applications implemented in new institutions. The impact of legacy applications requires accurate measurement to serve as a reference for further development. The IT Balanced scorecard was chosen to measure whether the implementation of the legacy IGRACIAS V.1 application has had an impact and development direction that is in line with the goals of the new institution. The results show that two domains based on the IT Balanced scorecard need improvement, namely User Orientation and Future Orientation.